2014
DOI: 10.4097/kjae.2014.67.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the APACHE IV model and its comparison with the APACHE II, SAPS 3, and Korean SAPS 3 models for the prediction of hospital mortality in a Korean surgical intensive care unit

Abstract: BackgroundThe Acute Physiology and Chronic Health Evaluation (APACHE) IV model has not yet been validated in Korea. The aim of this study was to compare the ability of the APACHE IV with those of APACHE II, Simplified Acute Physiology Score (SAPS) 3, and Korean SAPS 3 in predicting hospital mortality in a surgical intensive care unit (SICU) population.MethodsWe retrospectively reviewed electronic medical records for patients admitted to the SICU from March 2011 to February 2012 in a university hospital. Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 31 publications
0
42
0
5
Order By: Relevance
“…Two general prognostic models (APACHE-II and SAPS-3) and one cancer-specific prognostic model were evaluated in this study. APACHE-II, SAPS-3, and APACHE-II CCP models were chosen for comparisons because these models are currently used in our ICU and are one of the most popular models around the world [12][13][14]. According to the study objective, we found a better performance for APACHE-II CCP model than those for APACHE-II, SAPS-3, and SAPS-3 CSA models.…”
Section: Discussionmentioning
confidence: 97%
“…Two general prognostic models (APACHE-II and SAPS-3) and one cancer-specific prognostic model were evaluated in this study. APACHE-II, SAPS-3, and APACHE-II CCP models were chosen for comparisons because these models are currently used in our ICU and are one of the most popular models around the world [12][13][14]. According to the study objective, we found a better performance for APACHE-II CCP model than those for APACHE-II, SAPS-3, and SAPS-3 CSA models.…”
Section: Discussionmentioning
confidence: 97%
“…However, in a retrospective singlecenter study including patients from a surgical ICU in a Korean academic medical care center, the overall discrimination and calibration of APACHE IV were similar to those of APACHE II. 37 In a prospective single-center study comparing the performance of APACHE II and III from a neuro-ICU at Taichung Veterans General Hospital, the APACHE III provided better prediction for severe morbidity than the GCS and APACHE II for patients with acute head injury, 38 but an independent external validation of these results is pending. Another limitation may have been an underestimation of SE duration, especially with unwitnessed onset, which is often the case for nonconvulsive SE.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] In our daily clinical routine, we use APACHE II and SOFA scores to determine mortality, and the TISS-28 score is used by nurses in the ICU. The TISS-28 calculates the amount of nursing time spent on direct patient care and does not require any laboratory findings.…”
Section: Discussionmentioning
confidence: 99%